2020
DOI: 10.29333/ejgm/8323
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Phosphatase is not Associated with Insulin Resistance: A Retrospective Cross-Sectional Study

Abstract: Background: Many epidemiologic studies suggested that vitamin D deficiency is associated with obesity but the relationship between obesity and alkaline phosphatase (ALP) is controversial. In this study association between insulin resistance and alkaline phosphatase is investigated.Methods: Of the 124 women aged (35,942±9,714) years with (39,47±7,66) body mass index (BMI) and with vitamin D deficiency is included. The relationship among insulin, glucose, parathormone (PTH), calcium (Ca), alkaline phosphatase (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 21 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have linked serum ALP and insulin resistance, although the association is still controversial [20][21][22]. Gurler et al suggested that there was no significant difference between ALP levels in 124 female patients with or without insulin resistance [23]. Additionally, several studies reported that there was no significant association between ALP and incident diabetes [20,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have linked serum ALP and insulin resistance, although the association is still controversial [20][21][22]. Gurler et al suggested that there was no significant difference between ALP levels in 124 female patients with or without insulin resistance [23]. Additionally, several studies reported that there was no significant association between ALP and incident diabetes [20,24,25].…”
Section: Discussionmentioning
confidence: 99%